EXPRESSION OF CONCEPTIONS OF THE LITHUANIAN BOOK SCIENCE SCHOOL IN ACADEMIC COURSES - LIEPAITĖ, INGA (Knygotyra, 2010)
The unity of science and study is one of the oldest traditions of universities, which goes from the beginning of the nineteenth century when the representative model of Western academic institution – Berlin University – was established. The institution of Vilnius University in Lithuania intercepted and realized this tradition. We can find the beginnings of the formation of Lithuanian book science in the early nineteenth century at Vilnius University. The coming of book science and its further development proclaim a close contact of science and study of the book science. The academic courses of book science, lectured at Vilnius University up to now, and their supply of educational books were chosen as the object of research. The academic courses of bibliography and librarianship sciences stay behind the horizon of academic courses of book science by today conception of book science in its today’s conception. The aim of this article is to ascertain how conceptions formulated by participants of the Lithuanian book science school in the process of research are reflected in pedagogical practice. We chose the educational books as an intermediary factor which integrates the results of research and of pedagogical practice. The main conceptions of the LithuaAbstractnian book science school and their authors, the tendencies of development of academic courses of lecturing at Vilnius University and the complex of educational books used in the lecturing process of academic courses of book science by following the periodization of book science are analyzed. A conclusion is that the Lithuanian book science school and its role in the process of students’ training are closely linked spheres which are related by common history, institutions, events and people participating in these events. The identical periodization of Lithuanian book science, both in research and in pedagogical practice, enables studying these activities as a whole unit – the main identifying factor of the character of the scientific school. The educational books can be one of the formal channels of communication and fixation of research results and of transmission of knowledge to students. Analysis of the evolution of theoretical mind, of lecturing the academic courses and of textbooks allows to maintain that these three components not only strongly influence the development of each other, but also determine the formation, development and progress of such a complicated phenomenon as a scientific school.
Keywords: ...